The patterns of patents in China - Xie, Zhuan; Zhang, Xiaobo (International Food Policy Research Institute, 2014)
Innovations are a key driver of long-term economic growth. There has been an explosion of patent filings in China in the past three decades. But empirical studies on the pattern of innovations at the firm level are rather scant primarily due to lack of firm-specific patent data. We have made concerted efforts to match Chinese patent data with a large firm-level database. The matched dataset enables us to examine the patterns of patents at the firm level.